IDDAH DAN TANTANGAN MODERNITAS - Zulaikha, Siti (STAIN Jurai Siwo Metro, 2010)
Abstract`Iddah in Islamic law to determine cleanliness of the womb of a wife and an opportunity for couples who divorce to consider in determining positive and negative sides effect of divorce. But in reality not a few Muslims who ignore the `iddah law with a variety of reasons, such as avoiding fornication, need someone who can help the economy, even for reasons not aware of `iddah. Violations during the `iddah, certainly raises new problems in society. In this modern age have uterine conditions can be detected without having to wait up to three months, the question is still relevant og rule of law was `iddah today, then why the husband tends to abandon its obligations? This article shows that the `iddah has many virtues in various aspects, which each have a relationship that can not be separated. Developments in science and modern technology can not change the rule in cases that have been clearly expressed and defined by the Quran and Sunnah. ButÂ wat doubtful and adultery developments in science and just in caseÂ technology can be utilized, because the law between men and women in this case related only to the problem using the sanctity of the womb dukhÅ«l. Although there is the belief that the womb of the woman (wife) clean and in between them (husband and wife) can not reconcile. But women can not be justified for the (former wife) violated the provisions of `iddah.Â Keywords: `iddah, technology, Islamic law.